LINGUOCULTURAL CHARACTERISTICS OF PHRASEOLOGICAL UNITS IN MODERN ENGLISH AND UZBEK - Pazilova Nasibaxon Muhammadqosimovna,; Abdullayeva Sevara Xazratbek qizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article discusses the national and cultural features of phraseology. It also studies the classification of phraseology and interlingual correspondence under the influence of culture in English and Uzbek.